PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN DAN KARAKTERISTIK TENAGA PEMASAR TERHADAP MOTIVASI DAN KINERJA TENAGA PEMASAR PADA PT. BANK RAKYAT INDONESIA (PERSERO) Tbk. CABANG JOMBANG - Mokhamad Yanuar Pradita (Jurnal Bisnis dan Manajemen, 2017)
The purpose of this research is to know: 1) the effect of compensation on work motivation, 2) the influence of leadership style on work motivation, 3) influence of marketer's characteristic to work motivation, 4) influence of work motivation to marketer performance, 5) influence of compensation to performance marketers, 6) influence of marketer's characteristic on sales force performance, 7) influence of leadership style on marketer's performance, 8) influence of compensation to marketer's performance through motivation, 9) influence of leadership style on marketer's performance through motivation, the characteristics of marketers to marketers' performance through motivation. The sample of the study was 136 respondents taken with purposive sampling technique. Data analysis technique is done by SEM analysis.The results of this study are as follows: 1) Compensation has a significant negative effect on work motivation. 2) Characteristics of individual marketers have a significant positive effect on work motivation. 3) Leadership style has a significant positive effect on work motivation. 4) Motivation has a significant positive effect on performance. 5) Compensation has a significant negative effect on performance. 6) Characteristics of individual marketers have a significant positive effect on performance. 7) Leadership style has a significant positive effect on performance. 8) Work motivation mediates between compensation for performance. 9) Work motivation mediates between leadership styles on performance. 10) Work motivation mediates between the individual characteristics of the marketer's force on performance. DOI : https://doi.org/10.26905/jbm.v4i2.1697